The Impact of Corporate Governance on Operating Performance during Goods & Services Tax Implementation in Malaysia - Sitraselvi Chandren; Ayoib Che Ahmad; Arifatul Husna Mohd Ariff; Santhirasegaran Nadarajan (International Journal of Supply Chain Management, 2019)
The effectiveness of corporate governance provides a promising value creation to firm even during implementation of new policy for example during Goods & Services Tax (GST) implementation in year 2015. By embracing agency theory, this paper investigates five corporate governance variables relationship with operating performance (sales growth and current ratio) during and after GST implementation. This study examines 265 Malaysian listed firms for year 2015 (during) and 2016 (after) GST implementation period. The OLS regression results report that there is significant relationship of corporate governance in firm operating performance particularly during and after GST implementation. Board independent, CEO age and family CEO have positively contribute to sales growth during and after GST implementation. For working capital effectiveness during and after GST implementation, the CEO age and family CEO delineate significant positive association with operating performance (current ratio). This displays on the governance effectives in discharging their roles to strengthen operating performance particularly during a new financial or tax policy implementation that requires necessary changes in business processes. It uncovers the transparency of Malaysian corporate governance commitment and acceptance to GST for firm and country sustainable development. In sum, an effective governance system that supports the firm operating performance makes GST as a business friendly tax system.